Inequality, Institutions, and Informality - Alberto Chong; Mark Gradstein (Inter-American Development Bank, Research Department, 2004)
This paper presents theory and evidence on the determinants of the size of the informal sector. We propose a simple theoretical model in which the informal sector`s size is negatively related to institutional quality and positively related to income inequality. These predictions are then empirically validated using different proxies of the size of the informal sector, income inequality, and institutional quality. The results are shown to be robust with respect to a variety of econometric specifications.
Keywords: 330; Informeller Sektor; Schattenwirtschaft; Einkommensverteilung; Welt; Governance-Ansatz